A heat recovery anti-icing system for stationary gas turbines - Naylor, David, Ph. D. (Knovel, 2009)
One of the unique problems of operating gas turbines in cold climates such as that of Canada is inlet icing. A new heat recovery system provides better protection of the complete air inlet system as well as lower effective operating costs.
Keywords: Gas-turbines.; Ice prevention and control.; Heat recovery.; elektronické knihy; electronic books